Liquiritoside Alleviated Pb Induced Stress in Brassica rapa subsp. Parachinensis: Modulations in Glucosinolate Content and Some Physiochemical Attributes - Akram, Waheed; Khan, Waheed Ullah; Shah, Anis Ali; Yasin, Nasim Ahmad; Li, Guihua (Frontiers in Plant Science, 2021)
Current research was conducted to explore the effects of liquiritoside on the growth and physiochemical features of Chinese flowering cabbage (Brassica rapa subsp. parachinensis) under lead (Pb) stress. Lead stressed B. rapa plants exhibited decreased growth parameters, chlorophyll, and carotenoid contents. Moreover, Pb toxicity escalated the synthesis of malondialdehyde (MDA), hydrogen peroxide (H2O2), flavonoids, phenolics, and proline in treated plants. Nevertheless, foliar application of liquiritoside mitigated Pb toxicity by decreasing oxidative stress by reducing cysteine, H2O2, and MDA contents in applied plants. Liquiritoside significantly increased plant height, shoot fresh weight and dry weight, number of leaves, and marketable value of Chinese flowering cabbage plants exposed to Pb toxicity. This biotic elicitor also enhanced the proline, glutathione, total phenolics, and flavonoid contents in Chinese flowering cabbage plants exposed to Pb stress compared with the control. Additionally, total glucosinolate content, phytochelatins (PCs), and non-protein thiols were effectively increased in plants grown under Pb regimes compared with the control plants. Overall, foliar application of liquiritoside can markedly alleviate Pb stress by restricting Pb translocation in Chinese flowering cabbage.